REGULATORY BACKGROUND AND ICT ENVIRONMENTAL MANAGEMENT TOOLS: A LOOK FROM THE LITERATURE - Urrea-Castaño, Hernán
Caring for the environment has become highly relevant in recent times at the international, national and local levels, as a result of the great ecological problems that are becoming increasingly acute and progressively deteriorate the planet. In this sense, talking about environmental sustainability in the framework of the United Nations 2030 Agenda, implies the reduction damage to the environment, also, the role of natural resources and services ecosystems on human well-being, economic opportunity and resilience social and ecological. For this reason, the sustainable development goals (SDGs) have in order to work on the great challenges that humanity faces to ensure that all people have the same opportunities and can lead a better life without compromising our planet. Likewise, the National Service of Learning SENA has developed different strategies aimed at contributing, as an institution, to the environmental sustainability of the training centers and the community that surrounds them, thus contributing with solutions to the environmental quality of the region through the development of an integrated system that allows contributing to the mitigation and compensation of environmental damage that have been occurring. This article outlines a look from the review of literature in primary and secondary sources to know and understand the main regulations that regulate environmental issues, those organizations that are references in matter and the main findings of ICT-mediated tools, which seek to contribute to the measurement, mitigation and environmental impact. As of this review, It is intended to define the criteria and parameters for the development of a prototype that allows the Central Complex of the Antioquia Region to carry out an adequate control and registration of its environmental indicators in order to propose strategies with a high environmental impact.